2018
DOI: 10.1177/0971355717738589
|View full text |Cite
|
Sign up to set email alerts
|

Passion Inspires: Motivations of Creative Entrepreneurs in Creative Business Centres in the Netherlands

Abstract: This study focused on the context in which entrepreneurship in the cultural and creative industries (CCI) takes place. We investigated entrepreneurs' inspiration, which refers to a specific type of motivation that allows the transformation of creative ideas into creative products. To explain this, we operationalised 'passion for work', which measures how passionately engaged entrepreneurs are with their work, as well as 'localised passion', which measures the passion others in one's proximity have for their wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 63 publications
(88 reference statements)
4
54
0
Order By: Relevance
“…Entrepreneurial passion is a combination of abilities and emotions, such as joy, the enthusiasm that a person has to face business challenges and challenges (Biraglia & Kadile, 2017;Cardon, Wincent, Singh, & Drnovsek, 2009a). Recent studies have shown that barriers to creativity (intrinsic and extrinsic), such as fear of failure, introversion, self-mistrust, low self-esteem, and social stereotypes, seriously affect the full development of entrepreneurial passion (create, invent, and develop) (Bhansing, Hitters, & Wijngaarden, 2018;Biraglia & Kadile, 2017). These factors have been limiting the creation of new ventures in the university context, which has led universities to adopt new business strategies that allow them to have graduate students with a greater culture and entrepreneurial passion (Liu & Gu, 2017;Rosique-Blasco et al, 2018).…”
Section: The Barriers Of Creativity In the Entrepreneurial Passion Inmentioning
confidence: 99%
“…Entrepreneurial passion is a combination of abilities and emotions, such as joy, the enthusiasm that a person has to face business challenges and challenges (Biraglia & Kadile, 2017;Cardon, Wincent, Singh, & Drnovsek, 2009a). Recent studies have shown that barriers to creativity (intrinsic and extrinsic), such as fear of failure, introversion, self-mistrust, low self-esteem, and social stereotypes, seriously affect the full development of entrepreneurial passion (create, invent, and develop) (Bhansing, Hitters, & Wijngaarden, 2018;Biraglia & Kadile, 2017). These factors have been limiting the creation of new ventures in the university context, which has led universities to adopt new business strategies that allow them to have graduate students with a greater culture and entrepreneurial passion (Liu & Gu, 2017;Rosique-Blasco et al, 2018).…”
Section: The Barriers Of Creativity In the Entrepreneurial Passion Inmentioning
confidence: 99%
“…Comunian 2011;Grabher 2004). The notions of 'buzz' (Asheim, Coenen, and Vang 2007;Storper and Venables 2004) and noise (Grabher 2002b) expand this social aspect of clustering by seeing co-location not only in terms of direct collaboration, but also as a matter of simply 'being there' (Gertler 1995) and absorbing the 'psychological motivation' or 'localised passion' (Storper and Venables 2004;Bhansing, Hitters, and Wijngaarden 2018) of indirect in-group contact. However, clusters are also approached in terms of production, where the locality functions as a 'seal of quality' (Molotch 1996;Molotch 2002), authentic neo-bohemia (Lloyd 2002), or provides 'artistic dividend' (Markusen and Schrock 2006).…”
mentioning
confidence: 99%
“…Context, or in other words, the circumstances, conditions, situations or environments that are external to the respective phenomenon and enable or constrain it' (Welter, 2011, p. 167), may be an important factor in many entrepreneurial activities. A focus on the context may generate a deeper understanding of particular traits and behaviors and may highlight the influence of environmental elements such as location, while also providing insights into how entrepreneurs implement mechanisms related to their entrepreneurial drive (Bhansing, Hitters & Wijngaarden, 2018).…”
Section: Literature and Research Backgroundmentioning
confidence: 99%